Inactivation of mitochondrial MUL1 E3 ubiquitin ligase deregulates mitophagy and prevents diet-induced obesity in mice - Cilenti, Lucia; Di Gregorio, Jacopo; Mahar, Rohit; Liu, Fei; Ambivero, Camilla T.; Periasamy, Muthu; Merritt, Matthew E.; Zervos, Antonis S. (Frontiers in Molecular Biosciences, 2024)
Obesity is a growing epidemic affecting billions of people worldwide and a major risk factor for a multitude of chronic diseases and premature mortality. Accumulating evidence suggests that mitochondria have a profound role in diet-induced obesity and the associated metabolic changes, but the molecular mechanisms linking mitochondria to obesity remain poorly understood. Our studies have identified a new function for mitochondrial MUL1 E3 ubiquitin ligase, a protein known to regulate mitochondrial dynamics and mitophagy, in the control of energy metabolism and lipogenesis. Genetic deletion of Mul1 in mice impedes mitophagy and presents a metabolic phenotype that is resistant to high-fat diet (HFD)-induced obesity and metabolic syndrome. Several metabolic and lipidomic pathways are perturbed in the liver and white adipose tissue (WAT) of Mul1(-/-) animals on HFD, including the one driven by Stearoyl-CoA Desaturase 1 (SCD1), a pivotal regulator of lipid metabolism and obesity. In addition, key enzymes crucial for lipogenesis and fatty acid oxidation such as ACC1, FASN, AMPK, and CTP1 are also modulated in the absence of MUL1.The concerted action of these enzymes, in the absence of MUL1, results in diminished fat storage and heightened fatty acid oxidation. Our findings underscore the significance of MUL1-mediated mitophagy in regulating lipogenesis and adiposity, particularly in the context of HFD. Consequently, our data advocate the potential of MUL1 as a therapeutic target for drug development in the treatment of obesity, insulin resistance, NAFLD, and cardiometabolic diseases.